HIV SERO-POSITIVE STATUS AMONG CLIENTS AGED ≥ 50 YEARS THAT PRESENTED FOR CARE IN A TERTIARY HEALTH FACILITY IN NORTHEASTERN NIGERIA - Ajayi BB; Denue BA; Goni BW; Maduagwu SM; Oyinloye SO; Akawu CB; Kida IM; Ajayi OD; Dawurung JS (Ntec Specialist, 2013)
The introduction of highly active antiretroviral therapy (HAART) has transformed HIV infection from hopeless to manageable health condition comparable to non-infectious diseases such as asthma and diabetes mellitus. This modest achievement has reduced morbidity and mortality and increased longevity and quality of life among HIV infected persons. Although reports from developing countries such as Nigeria, shows that youth within the reproductive are most affected by the scourge of HIV/AIDS. Older patients with features that may be indicative of HIV infection are often overlooked in favour of other differential diagnosis. Objective: To document HIV positive sero-status among client aged 50 years and above that necessitated HIV test as part of their clinical evaluation after voluntary counseling and testing at a tertiary health facility. Method: Record of 1674 adults participants that presented for care between January 2009 - December 2013, were retrieved for this study. Results: The HIV-seropositive status among the participants was 370 (22.1%). It showed a female preponderance of 136 (26.0%) than 234 (20.0%) in males. The peak annual prevalence was observed in the year 2010, steady decline was observed thereafter. Overall, older participants between 60-70 years had higher HIV-seropositivity status. This study shows one out of four males and five females with index of suspicion either based on clinical presentation or risky sexual behavior are positive for HIV infection. Conclusion: This report underscores the need to explore other risk factors that may be peculiar to older segment of the society and introduce HIV intervention strategies for the older populations. Delivery of HIV intervention measures and services to this segment of the population is expedient. Measures and interventions should take into consideration the peculiarities, specific vulnerabilities and HIV-related challenges faced by this group of clients